1999
DOI: 10.2116/analsci.15.23
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 210Pb and 210Po in Environmental Samples by Alpha Ray Spectrometry Using an Extraction Chromatographic Resin

Abstract: 210 Po (t 1/2 =138.38 d) occurs naturally via 210 Pb (t 1/2 =22.3 y) and 210 Bi (t 1/2 =5.15 d) in the 238 U decay chain. The contribution of 210 Pb, 210 Bi and 210 Po to the internal radiation dose to human has been estimated to be around 8%.1 Various analytical methods have been applied to the separation and determination of 210 Po. 2,3 Recently, a crown ether loaded extraction chromatographic resin (EiChroM Sr.Spec™) was applied to the selective separation of Pb and Po in several samples. Vajda et al. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…The observed concentrations of 210 Po and 210 Pb in seaweeds of the Mallipattinam ecosystem are comparable with the reported values from the Mandapam (Somasundaram, 1998) and Tuticorin (Krishnamookthy et al, 2008) ecosystems. Miura et al (1999) reported that the 210 Po value for the seaweed Gelidium amansii was 10 Bq kg À1 , which is also comparable with our results. For sea grass (Cymadocea serrulata), the activities of 210 Po and 210 Pb were 11 and 2 Bq kg À1 , respectively.…”
Section: Resultssupporting
confidence: 92%
“…The observed concentrations of 210 Po and 210 Pb in seaweeds of the Mallipattinam ecosystem are comparable with the reported values from the Mandapam (Somasundaram, 1998) and Tuticorin (Krishnamookthy et al, 2008) ecosystems. Miura et al (1999) reported that the 210 Po value for the seaweed Gelidium amansii was 10 Bq kg À1 , which is also comparable with our results. For sea grass (Cymadocea serrulata), the activities of 210 Po and 210 Pb were 11 and 2 Bq kg À1 , respectively.…”
Section: Resultssupporting
confidence: 92%
“…The method combines procedures from Refs. [7][8][9]21]. Briefly 30 ml of concentrated HNO 3 and 1 ml of 209 Po tracer were added to 1 g of solid samples (soil, sediment, etc.).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the samples were processed by microwave acid digestion under pressure [7][8][9] and radiochemical separation in order to isolate 210 Po. Results of the same samples previously measured for 210 Pb are used to verify the self-attenuation correction methods.…”
Section: Introductionmentioning
confidence: 99%
“…Polonium in trace quantities can be catholically deposited on different electrodes with a suitable current density from a verity of electrolytes. (Meyer & Schweidler, 1906, Paneth & Hevesy, 1913Broda & Wright, 1946;Miura, Kawabe, & Kirita, 2000). Kihara, Yoshida, and Matsui (1988) have studied electro deposition of polonium and the interaction between deposited polonium and based electrode material.…”
Section: Electro Depositionmentioning
confidence: 99%